A higher levels multilevel inverter with reduced number of switches. Issue 8 (3rd August 2018) - Harbi, I. A.; Azazi, Haitham Z.; Lashine, Azza E.; Elsabbe, Awad E.
ABSTRACT: This paper presents a high-levels multilevel inverter (MLI) with a reduced number of the required switches. Forty-nine levels can be obtained in the output voltage from this circuit by using only 12 semiconductor switches, while in conventional topologies of MLI, a higher number of switches is required producing a lower number of levels in the output voltage. Reduction in the number of semiconductor switches, gate drivers, DC voltage sources and increasing the number of voltage levels are advantages of the proposed MLI compared with other topologies. These advantages result in smaller size, lower loss and low installation cost. Total harmonic distortion (THD) in the output waveform of the inverter is very low, thus, using a filter to improve the output waveform is not needed. A switching pulse system has been presented to produce nearly sinusoidal waveforms. Mathematical relations and switching states of the proposed topology have been discussed. Simulation results have been obtained and studied. The prototype of the modified MLI has been built and tested in the laboratory using a dSPACE (DS1104) evaluation board in order to verify the simulation results. Several of the experimental results of the proposed topology have been included and discussed.